Use of decision‐support tools by students to link crop management practices with greenhouse gas emissions: A case study. Issue 2 (10th July 2021) - Jabbour, Randa; McClelland, Shelby C.; Schipanski, Meagan E.
Abstract: Global food systems contribute to greenhouse gas emissions, and the mitigation of these emissions is a critical component of addressing the challenge of climate change. A variety of decision‐support tools are available for agricultural producers to use to estimate how their management decisions affect emissions. These tools, often free and online, can be incorporated into agriculture and natural sciences courses, providing an engaging and interactive way for students to learn about climate change mitigation in online courses. Here, we focus on three tools: COMET‐Planner, COMET‐Farm, and Cool Farm Tool. Each of these tools link agricultural management with estimated emissions but differ according to the scope of analysis and type of functionality. Our case study navigates how to best incorporate each tool into undergraduate courses ‐ providing detailed examples focused on crop production. Teaching notes provide guidance on pairing these activities with lessons related to agricultural policy, science communication, and farm nutrient budgets. Instructors have considerable opportunity to incorporate agricultural decision‐support tools into courses to support students connecting scientific concepts to real‐world application. Core Ideas: Students can learn about both climate change mitigation and adaptation in agriculture courses. Free, online tools provide a way to estimate greenhouse gas emissions due to agriculture. Simulating farm management scenarios can foster systems‐thinking. Decision‐support tools designed for land managers offer students real‐life connections.